Investment Analysis Upgrading Capacity of Produced Water Treatment System (PWTS) at a Gas Processing Facility - I Made Bayu Sukma Firmanjaya; I Ketut Gunarta (Publikasi Indonesia, 2025)
The oil and gas industry remains a strategic pillar for national energy security, yet it faces significant operational challenges as production fields mature. A critical issue is the exponential increase in produced water, which often surpasses the design limits of existing Produced Water Treatment Systems (PWTS). This research evaluates the investment feasibility of upgrading the PWTS capacity at a major gas processing facility where current water production has reached 3,110 BWPD, significantly exceeding the 2,000 BWPD design capacity. To address this, a hybrid framework was developed by integrating Technical and Economic Risk Assessments. Technical risks were quantified using Failure Mode and Effect Analysis (FMEA), involving 28 failure modes across seven primary equipment units. To mitigate the subjectivity of expert judgment, a Monte Carlo Simulation with 10,000 iterations was implemented, followed by a Risk Matrix to translate technical failures into quantifiable